Antimutagenic Effect of Hibiscus sabdariffa L. Aqueous Extract on Rats Treated with Monosodium Glutamate - Ana Carla Guidini Valentini Gheller; Jacqueline Kerkhoff; Gerardo Magela Vieira Júnior; Kleber Eduardo de Campos; Marina Mariko Sugui (The Scientific World Journal)
Hibiscus sabdariffa L. is a plant of the Malvaceae family, commonly known as roselle. H. sabdariffa is known to contain antioxidant, cholesterol-lowering, antiobesity, insulin resistance reduction, antihypertensive, and skin cancer chemopreventive properties. This study evaluated the effects of H. sabdariffa aqueous extract against cyclophosphamide (CPA, 25 mg/Kg) induced damage to DNA in male Wistar rats by micronucleus test. Samples of H. sabdariffa calyx were obtained in the municipality of Barra do Garças, Mato Grosso, Brazil. The aqueous extract was prepared by infusion and each animal received a daily dose of 400 mg/Kg by gavage for 15 consecutive days of treatment. The presence of anthocyanins was confirmed by ferric chloride test and phenolic compounds using high-performance liquid chromatography, with emphasis on the identification of rutin. The animals were sacrificed by deepening of anaesthesia to obtain bone marrow and determination of the frequency of micronucleated polychromatic erythrocytes. The group treated with the aqueous extract of H. sabdariffa revealed a 91% reduction in micronucleus frequency when compared with the positive control group. Under the conditions tested, H. sabdariffa L. presented a protective effect to CPA-induced damage to DNA of the treated animals, and it is a potential candidate as a chemopreventive agent against carcinogenesis.